(untitled) (Al-Academy, 2020)
The expressive discourse, in the form of the rural singing, is considered one of the interactive framework and the metaphorical dialogues in creating the aesthetic climate that connects the circles of its basic elements, singing, playing music, expression, costumes, sham movements and so forth. The rhetorical language in this field includes all those parts and turns them into an integrated idea within the culture of the musical science, specifically the heart of the rural singing. This research dealt with a number of topics of relevance in the expressive discourse for the form of the rural singing. The first chapter consists of the methodological framework of the research, represented by the research problem, importance and aim, in revealing the rhetorical expression as a necessity of the cultural environments and the title of the societies and civilizations. Chapter two consists the theoretical framework represented by the following: (the rhetorical discourse, the rural singing). The third chapter is the research methodology, community and sample and an analysis of a model of the rural genre (Chabeer al-koun genre), by Farraj Wahab, as it is part of the expressive discourse in the rural singing. The researched came up with a number of results and conclusions, and put forward a set of suggestions and recommendations. Finally the research ended with a list of sources